Mixed-methods survey of healthcare workers’ experiences of personal protective equipment during the COVID-19 pandemic in Aotearoa/New Zealand - Wild, CEK; Wells, H; Coetzee, N; Grant, CC; Sullivan, TA; Derraik, JGB; Anderson, YC (MDPI, 2022)
There have been widespread issues with the supply and distribution of personal protective equipment (PPE) globally throughout the COVID-19 pandemic, raising considerable public concern. We aimed to understand the experiences of healthcare workers using PPE during the first COVID-19 surge (February–June 2020) in Aotearoa/New Zealand (NZ). This study consisted of an online, voluntary, and anonymous survey, distributed nationwide via multimodal recruitment. Reported domains included PPE supply, sourcing and procurement, fit-testing and fit-checking, perceived protection, trust and confidence in the workplace, mental health, and the likelihood of remaining in the profession. Differences according to demographic variables (e.g., profession and workplace) were examined. We undertook a descriptive analysis of responses to open-text questions to provide explanation and context to the quantitative data. The survey was completed in October–November 2020 by 1411 healthcare workers. Reported PPE shortages were common (26.8%) among healthcare workers during surge one in NZ. This led to respondents personally saving both new (31.2%) and used (25.2%) PPE, purchasing their own PPE (28.2%), and engaging in extended wear practices. More respondents in the public system reported being told not to wear PPE by their organisation compared with respondents in the private sector. Relatively low numbers of respondents who were required to undertake aerosol-generating procedures reported being fit-tested annually (3.8%), a legal requirement in NZ. Healthcare workers in NZ reported a concerning level of unsafe PPE practices during surge one, as well as a high prevalence of reported mental health concerns. As NZ and other countries transition from COVID-19 elimination to suppression strategies, healthcare worker safety should be paramount, with clear communication regarding PPE use and supply being a key priority.